Perkembangan Teknologi Digital dalam Kedokteran Gigi Forensik - Tri Meilana, Andi Nur Sakina; Auerkari, Elza Ibrahim; Suhartono, Antonius Winoto (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2025)
In this modern era, technology continues to grow rapidly and has become part of our everyday life. Recent advances have popularized various digital technologies for their use in forensic dentistry, especially to assist individuals. Various digital recovery methods have been included including replacing conventional forensic methods in terms of acquisition, analysis, efficiency, and accuracy. This review aims to discuss the development of digital technology within the scope of forensic dentistry as well as various methods through digital technology that can be used in solving various forensic cases. The writing of this review was carried out through a literature review on various databases in the form of PubMed, SciELO, MEDLINE, and Scholar within the last 10 years. Various digital developments in forensic dentistry that have been published include radiography and digital photography, reconstructing fragments with 3D Printing, Intra Oral 3D Scanners, UV photography in aid of dental materials, superimposed methods, assisted digital prostheses, virdentopsy & teledentistry, as well as various device developments software and database. Of these various methods, almost all methods produce good accuracy, simpler methods without any destructive action on forensic evidence, and save time compared to conventional methods. However, no method has been universally applied worldwide. This is due to limitations in accessing tools and costs that are not relatively cheap. In the future, digital technology will play a crucial role in forensics especially if it can be accessed easily.